An Analysis on the Preschool Teachers’ Views on the Creative Leadership Skills of the School Administrators - BALABAN DAĞAL, ASUDE (My University, 2023)
This research aims to analyze the differences between the views of the teachers working in pre-school education institutions on the creative leadership skills of the school administrators within the framework of variables such as age, educational background, type of the educational institution, duration of employment, the age group of the pre-school children, life index and duration of employment at the current educational institution. Research data in this correlational research were collected from 140 pre-school teachers. Data were collected with the \"Creative Leadership Scale\" developed by Dikmen Ada (2012). The internal consistency coefficient of the scale is 0.986. The results of the research revealed that school administrators are highly creative leaders. Teachers with lower seniority were found to have positive opinions in the \"focusing on change and transformation\" sub-dimension with regard to their school administrators. However, pre-school teachers were observed to be relatively distant to the concept of creative leadership.
Keywords: Sosyal ve Beşeri Bilimler; Psikoloji; Eğitim; Social Sciences and Humanities; Psychology; Education; Temel Bilimler (SCI); Sosyal Bilimler (SOC); Sosyal Bilimler Genel; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Natural Sciences (SCI); Social Sciences (SOC); PSYCHOLOGY; SOCIAL SCIENCES, GENERAL; EDUCATION & EDUCATIONAL RESEARCH; Psikoloji (çeşitli); Genel Psikoloji; Sosyal Bilimler ve Beşeri Bilimler; Psychology (miscellaneous); General Psychology; Social Sciences & Humanities